PSIKOLOGI ORGANISASI DAN PENGARUHNYA TERHADAP BUDAYA KERJA DI MTSN 1 SUMEDANG - Teguh Iqbal Maulana; Mulyawan Safwandy Nugraha (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2026)
Objective: This study examines the influence of organizational psychology on work culture at MTsN 1 Sumedang, focusing on motivation, communication, conflict management, and leadership within an Islamic educational context. Methods: A qualitative case study approach was employed, using purposive sampling. Data were collected through in-depth interviews with a senior teacher (Ibu Eva), participant observation, and documentation analysis, then analyzed using Miles, Huberman, and Saldaña’s interactive model. Results: The findings reveal that although the term "organizational psychology" is not formally recognized, its core principles are organically integrated into daily management practices. A healthy, non-toxic work environment, mutual support among colleagues, periodic appreciation programs, and spiritual routines such as communal prayers and monthly religious gatherings significantly enhance teacher motivation and well-being. Novelty: This research contributes a contextual model demonstrating how modern organizational psychology principles such as intrinsic motivation, collaborative communication, and participative leadership can be authentically integrated with Islamic educational management principles like itqan (professionalism), syura (consultation), and amanah (trustworthiness).